2016
DOI: 10.1111/eje.12245
|View full text |Cite
|
Sign up to set email alerts
|

Capturing differences in dental training using a virtual reality simulator

Abstract: Virtual reality simulators are becoming increasingly popular in dental schools across the world. But to what extent do these systems reflect actual dental ability? Addressing this question of construct validity is a fundamental step that is necessary before these systems can be fully integrated into a dental school's curriculum. In this study, we examined the sensitivity of the Simodont (a haptic virtual reality dental simulator) to differences in dental training experience. Two hundred and eighty-nine partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(115 citation statements)
references
References 26 publications
2
108
0
5
Order By: Relevance
“…While it is recognised that expert performance is faster than novice performance [10,11], the converse is not necessarily true, i.e. faster performance does not necessarily confer better quality surgery [54,55]. The same applies to simulator-generated metrics; for example, while experts tend to have smoother movements, having smoother movements does not necessarily mean the operator is an expert.…”
Section: The Warm-up Tasksmentioning
confidence: 99%
“…While it is recognised that expert performance is faster than novice performance [10,11], the converse is not necessarily true, i.e. faster performance does not necessarily confer better quality surgery [54,55]. The same applies to simulator-generated metrics; for example, while experts tend to have smoother movements, having smoother movements does not necessarily mean the operator is an expert.…”
Section: The Warm-up Tasksmentioning
confidence: 99%
“…Outro estudo com alunos da School of Dentistry at the University of Leeds (Mirghani et al, 2016) foi realizado entre estudantes do primeiro, terceiro, quarto e quinto anos de graduação, utilizando-se o Simodont para avaliar a capacidade do simulador de diferenciar estudantes com variados níveis de experiência no mundo real. Utilizando dados fornecidos pelo sistema, o desempenho dos alunos foi analisado enquanto realizavam um procedimento simples no simulador.…”
Section: Outros Simuladores Para Treinamento Odontológicounclassified
“…The simulator integrates tactile sense in practice in a manner different from that by other VRS techniques 13,14) . Earlier research has indicated that Simodont® is useful for practicing dental treatments and can be used as equipment for training and acquiring research data 15) .Studies on using Simodont® for dental education have been published, but no research on the relationship between Simodont® and manual dexterity has yet been reported [16][17][18] . This study is the first to discuss this subject.…”
Section: Simodont® As Evaluation Equipmentmentioning
confidence: 99%